2018
DOI: 10.4236/health.2018.102017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Health Related Quality of Life, Quality of Sleep, and Oral Health Condition

Abstract: Japan's aging rate (ratio of elderly aged 65 and older to total population) has exceeded 20%. The aim of this study was to clarify the relationships between Health Related Quality of Life (HRQOL), Body Mass Index (BMI), and sleep quality. Subjects were 51 adults over 55 years old with chronic disease who living in the community. Instruments and structured interviews were used giving due consideration to privacy. Interviews were conducted within 10 -20 minutes at the out-patient department. The evaluation instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Theoretical classes (introduction of concepts of oral health, with use of play material to illustrate the components of the mouth, chewing and swallowing) would be carried out; with dolls to (re) see the processes of digestion of the human being, from tasting/olfaction, to mastication/deglutition, degradation and elimination of residues; on the importance of oral hygiene to maintain proper health and chewing capacity; concepts of healthy eating for the elderly, with different properties and consistencies of food; execution of basic cooking techniques that improve the food according to chewing capacity, and the different possibilities of food preparation with the use of appropriate cooking techniques. Sato et al (2018) says that there is a strong relationship between Quality of Life, Quality of Sleep and Oral Health Conditions in Japan's elderly population, as observed in other studies, and "people with low oral health-related QOL exhibit poor sleep quality". We can also observe the relation between low oral care and infections/immunity alterations, leading to a poor quality of life.…”
Section: ) Skin Care For the Elderly (Campos)mentioning
confidence: 78%
“…Theoretical classes (introduction of concepts of oral health, with use of play material to illustrate the components of the mouth, chewing and swallowing) would be carried out; with dolls to (re) see the processes of digestion of the human being, from tasting/olfaction, to mastication/deglutition, degradation and elimination of residues; on the importance of oral hygiene to maintain proper health and chewing capacity; concepts of healthy eating for the elderly, with different properties and consistencies of food; execution of basic cooking techniques that improve the food according to chewing capacity, and the different possibilities of food preparation with the use of appropriate cooking techniques. Sato et al (2018) says that there is a strong relationship between Quality of Life, Quality of Sleep and Oral Health Conditions in Japan's elderly population, as observed in other studies, and "people with low oral health-related QOL exhibit poor sleep quality". We can also observe the relation between low oral care and infections/immunity alterations, leading to a poor quality of life.…”
Section: ) Skin Care For the Elderly (Campos)mentioning
confidence: 78%
“…These results were comparable with those of a study by Choi et al, which found that the more patients perceived their saliva amount to be insufficient, the lower their reported OHRQoL [ 46 ]. Other studies have also reported that deteriorating dry mouth results in lower OHRQoL in older adults [ 9 , 11 , 23 , 36 ]. Notably, the present study revealed a correlation between xerostomia and CODS after controlling for BMI.…”
Section: Discussionmentioning
confidence: 98%
“…Several medications, including antihypertensive drugs, have an influential and dose-dependent association with xerostomia [ 22 ]. Medication for HT-induced hyposalivation might decrease self-cleansing and enhance dental caries susceptibility, leading to pulpal disease [ 36 ]. Generally, apart from experiencing xerostomia, participants with dental disease, especially pulpal disease, may have a higher chance of experiencing pain that impacts QoL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations